Strategies to enhance the integration of health services, education, research and community engagement within the Nursing Center Model - Neti Juniarti; Jeffrey Fuller (Jurnal Keperawatan Padjadjaran, 2025)
The Nursing Center (NC) Model is an innovative approach that integrates community engagement, education, research, and community health care services.  We have identified a conceptual framework for a client-centered, service-learning-oriented nursing curriculum that revitalizes community health nursing and improves services through integrated practice and research. The six stages of integration approaches include preparation, orientation, working, pre-termination, termination, and adoption.  Implementing these strategies can enhance the quality of nursing services, nursing graduates, and the health of people in the community.  To improve outcomes for all stakeholders involved, the Academic Health System (AHS) may also incorporate the NC model within the system.